Optimalisasi Hasil Belajar Siswa Melalui Pembelajaran Interaktif Berbasis Game dan Literasi di Sekolah Dasar Negeri 08 Salimpaung - Yarisda Ningsih; Nur azmi Alwi; Intan Resnika; Nabila Isya Farhan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
In the era of modern education, teachers are expected to create a creative and interactive learning environment. One approach that is increasingly being implemented is game-based learning combined with literacy enhancement at the elementary school level. This study aims to evaluate the effectiveness of this method in improving student learning outcomes. Data were collected through interviews with teachers at SDN 08 Salimpaung and supported by literature from ten scientific journals. The analysis results indicate that this strategy can improve student participation, conceptual understanding, and learning motivation.